(untitled) (Marketing Journal, 2025)
This paper conducted a comparative analysis of dynamics and changes in main indicators of the well -being of the population in Uzbekistan. Studied the differences in dynamic changes in total and real total per capita incomes in Uzbekistan across regions. In addition, studied impact of changes on sustainability based on results of statistical analysis of total and real total per capita incomes across regions.